If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 2t + -3w = 24 Reorder the terms: 2t + -3w + 10x = 24 Solving 2t + -3w + 10x = 24 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3w' to each side of the equation. 2t + -3w + 3w + 10x = 24 + 3w Combine like terms: -3w + 3w = 0 2t + 0 + 10x = 24 + 3w 2t + 10x = 24 + 3w Add '-10x' to each side of the equation. 2t + 10x + -10x = 24 + 3w + -10x Combine like terms: 10x + -10x = 0 2t + 0 = 24 + 3w + -10x 2t = 24 + 3w + -10x Divide each side by '2'. t = 12 + 1.5w + -5x Simplifying t = 12 + 1.5w + -5x
| 64s^2-81d^2= | | 2*6w=140 | | 300x-y=130 | | z^2+2z=2(z+2) | | 14(x+y)=14(y+x) | | 4(b-5)-3b=8 | | 2(3x-3)+5(2x+1)=1 | | 0.44x+3=2-0.3x | | 4x-1=2x+41 | | 7.56=(x*0.1)+(x*0.1*1.8) | | 0.02+0.5(x-2)=5.32 | | 0.8w=48 | | =(x*0.1)+(x*0.1*1.8) | | 5+(4x+17)=(5+4x)+17 | | 0.002+0.5(x-2)=5.32 | | 4y+2y+10=(y-5) | | 18c^2-33c=-14 | | 0.15x+0.06(7000-x)=690 | | (14-2x)(20-2x)(x)=230 | | 1.3+0.2x=0.5x-2.9 | | 3(2x-3)+4=27 | | (2x-4)3=5x | | 3x-160=0 | | 9m-(5+2m)= | | c-0.35c=91 | | 3(x-4)+2(3-x)=12 | | -48=-5(4+4)+8(x-8) | | 6-3m=5(2-m) | | 3(x+4)+2(3-x)=12 | | 3(p+7)-(4p-1)=-5(2p-6) | | -x+6y=-26 | | 5t-1=14 |